Groundwater quantity and quality assessment for aquifer recharge in Ohangwena region, Namibia - Ndakola, Hilja (Department of Civil Engineering, 2023)
The high population growth rate and changing climatic conditions for the Ohangwena region create increasing pressure on the local water balance. As groundwater demands increase and availability declines, sustainable groundwater management is required for the Ohangwena region. This thesis assessed the suitability of using runoff for aquifer recharge to augment groundwater in the Ohangwena region and minimize the lowering of water table. The Geographical Information System (GIS) and groundwater flow models were used in this study to assess the water resources in the study area. A multicriteria approach using a weighted rating was used in this study to generate a map showing areas suitable for groundwater recharge. The resultant groundwater potential recharge zones map was produced based on the overall weights of seven influential factors for groundwater recharge namely lithology, land use/land cover, lineaments, drainage, slope, geology, and soil type. The results of the assessment indicated that 85% of the Ohangwena region is characterized by high groundwater recharge zones, while 25% is characterized by very high groundwater recharge zones. The very high groundwater recharge zones are mostly found in the central part of the region, on the far upper western side and the eastern side of the region. The recorded recharge rates for the region in the range of 40 – 60 mm/year were introduced to an established model using the MODFLOW software, to assess the impact of Aquifer Recharge on the groundwater levels. The impact was assessed with both the steady-state model to approximate aquifer recharge under controlled conditions, and the transient state model for close representation of recharge in reality at four wells namely, WW201045, WW201637, WW201634, and WW20267, where it was evaluated by the hydraulic heads and water budget analysis. The steady state model results indicated a change in groundwater levels in the range of -0.10 - 0.70 m. In the same manner, the transient state model results show a gradual increase in groundwater levels in the range of 9.2 - 12.10 meters for the 350 m deep Ohangwena aquifer. The groundwater levels can be improved locally by infiltrating runoff into the KOH-II aquifer via the injection wells or infiltration basins during the rainy season (November to April) when there is plenty of runoff and flood in the region. The high soil infiltration rates in the region make runoff to be suitable for Aquifer Recharge implementation in the region. Transferring runoff to the aquifer aims at making use of the large aquifer storage space and limiting evaporation loss. The study also employed particle tracking and MT3DMS to assess the transport of contaminants associated with runoff within the aquifer. This was assessed at two wells thatserved as injection wells in the model, and four contaminants namely chloride, Electrical Conductivity, Total Dissolved Solids, and E-coli were studied. The outcomes of this assessment indicated that both Chloride, Electrical conductivity, Total Dissolved Solids, and E-coli concentrations decrease from 1000 mg/l to 0.01 mg/l, 532 mS/s to 0.1, 478.56 mg/l to 0.01 mg/l, and 9.58 to 0.01 respectively as timesteps increase, and it takes 20 timesteps (94672800 seconds) for them to disperse further into the aquifer. The dispersion of Chloride, EC, TDS, and E-coli within the aquifer covers a maximum distance of 12.1, 9.6, 8.7, and 6.7 km respectively.